A Digital Environment for Empowering the Main Actors of the Deep Energy Retrofitting Value Chain - Paolo Luigi Scala (AIDIC Servizi S.r.l., 2021)
The H2020 HAPPEN project has defined a new approach to tackle significant unsolved bottlenecks affecting the energy renovation markets of the residential built stock in the Mediterranean area: the MedZEB approach (Mediterranean way to nearly Zero Energy Building), which backbone is the HAPPEN ICT Platform. The paper describes firstly the MedZEB concept as a holistic, flexible and cost-optimal approach especially tailored for the Med area. It then presents the HAPPEN Platform in terms of general architecture, workflows, resources and tools aimed at fostering the spread of the MedZEB approach by integrating technical, financial, environmental and operational aspects. A critical assessment on the state-of-the-art highlights the novelty of the HAPPEN Platform as a comprehensive and effective framework for empowering the evolution of the Med renovation markets, as means for fostering the progressive uptake of deep energy retrofitting in the Med area.